Range of motion and ankle injury history association with sex in pediatric and adolescent athletes - Sugimoto, D.; McCartney, R. E.; Parisien, R. L.; Dashe, J.; Borg, D. R.; Meehan III, W. P. (The Physician and Sportsmedicine, 2018)
Background: Ankle sprain is one of the most common musculoskeletal injuries among young athletes, and there remains a gap in the literature regarding susceptibility to such injuries among physically active youth.